Epigenetic Regulation of Innate Immunity by microRNAs - Boosani, Chandra S. (Antibodies (Basel), 2016)
The innate immune response, which is usually referred to as the first line of defense, protects the hosts against pathogenic micro-organisms. Some of the biomolecules released from the pathogens, such as proteins, lipoproteins and nucleic acids, which are collectively termed as pathogen-associated molecular patterns (PAMPs), elicit signaling mechanisms that trigger immune responses in the hosts. Pathogen recognition receptors (PRRs) on the host cells recognize these PAMPs and initiate intracellular signaling through toll-like receptors (TLRs), RIG-I-like receptors (RLRs), and other pathways which induce production of pro-inflammatory cytokines and type I interferons. Recently, different members of tripartite motif containing proteins (TRIM) family of proteins were identified to intercept and regulate these cellular pathways. Specific targets of TRIM proteins have been identified and their molecular mechanisms were unraveled and identified unique domains involved in protein-protein interactions. Though innate immunity represents a tight and well conserved immune system in the host, gene expression in innate immunity was identified to be influenced by several epigenetic mechanisms including regulation by microRNAs (miRNAs). In this review, we present critical analysis of the findings on the identification of specific miRNAs that modulate expression of target genes involved in the regulation of innate immunity.